Construction and validation of a serious game about human papillomavirus infection. - Pereira Rodrigues Maciel, Maylla; Almeida Costa, Lílian Maria; Jardel Feitosa Sousa, Kayo Henrique; da Silva Oliveira, Adélia Dalva; Miranda Amorim, Fernanda Cláudia; Batista Moura, Luana Kelle; Gollner Zeitoune, Regina Célia; Aparecida Pinheiro Landim Almeida, Camila (Acta Paulista de Enfermagem, 2022)
Objective: To describe the process of construction and validation of a serious game for the prevention of infection caused by human papillomavirus. Methods: This is a methodological study that followed the steps: conceptualization, pre-production, prototyping, production and expert assessment. For conceptualization and pre-production, an integrative review was developed, which generated demands for knowledge, categorized and used in the prototype production. In an expert assessment, 13 participated for content analysis and seven for design, who answered different instruments. Data were analyzed for the score of Suitability Assessment of Materials and Content Validity Index. Results: A serious game was developed based on gaps in population's knowledge identified in the literature, called electronic roulette. Content experts considered that the technology developed has potential for health education and prevention of forms of illness caused by the human papillomavirus. For assessing appearance, design experts found the understandability and quality of the interface satisfactory. Conclusion: Electronic roulette presented satisfactory evidence of content validity. The recommendations of the experts improved the content and appearance, enabling the mediation of educational activities.